A systematic review and meta-analysis of unilateral versus bilateral pedicle screw fixation in transforaminal lumbar interbody fusion. - Xu-Qi Hu; Xin-Lei Wu; Cong Xu; Xu-Hao Zheng; Yong-Long Jin; Li-Jun Wu; Xiang-Yang Wang; Hua-Zi Xu; Nai-Feng Tian (PLoS ONE)
Background Transforaminal lumbar interbody fusion (TLIF) has become one of the most widely used procedures for lumbar spinal disorders. However, it is still unclear whether TLIF with unilateral pedicle screw (PS) fixation is as effective as that with bilateral PS fixation. We performed a meta-analysis of the literatures and aimed to gain a better understanding of whether TLIF with unilateral PS fixation was safe and effective for lumbar diseases. Methodology/principal findings We systematically searched Ovid, Springer, and Medline databases for relevant randomized controlled trials (RCTs) that compared the clinical and radiological outcomes of unilateral versus bilateral PS fixation in TLIF. Risk of bias in included studies was assessed using the Cochrane Risk of Bias tool. We generated pooled risk ratios or weighted mean differences across studies. According to our predefined inclusion criteria, seven RCTs with a total of 441 patients were included in this study. Baseline characteristics were similar between the unilateral and bilateral groups. Our meta-analysis showed that no significant difference was detected between the two groups in terms of postoperative clinical function, fusion status, reoperation rate, complication rate, and hospital stay (p>0.05). Pooled estimates revealed that the unilateral group was associated with significantly reduced implant cost, operative time and blood loss (p<0.05). Conclusions/significances Our meta-analysis suggested TLIF with unilateral PS fixation was as safe and effective as that with bilateral PS fixation for lumbar diseases in selected patients. Despite these findings, our meta-analysis was based on studies with small sample size and different study characteristics that might lead to the inconsistent results such as various functional outcomes among the included studies. Therefore, high-quality randomized controlled trials with larger sample size are also needed to further clarify these issues and to provide the long-term outcomes.